PENINGKATAN KAPASITAS MAHASISWA DALAM MENGHADAPI PELUANG DAN TANTANGAN DI ERA TRANSFORMASI DIGITAL SOCIETY 5.0 - Chandra Lukita; Stefanny Christina; Sudadi Pranata; Agung Supriyadi (Jurnal Abdi Insani, 2022)
Humans underwent a massive transformation and launched themselves into a fully modern and digital approach to society. But on the other hand there are threats in the advancement of the application of this digital technology. The purpose of this community service is to provide education about the opportunities and challenges for lecturers and students in dealing with changing times in the Era of Digital Society Transformation 5.0. This service activity was carried out through a web seminar due to the Covid-19 pandemic. This activity was organized by Catur Insan Cendekia University and Cirebon City ICT Volunteers. This activity was attended by lecturers and students from, West Java, DKI Jakarta, Central Java and East Java. The method of implementing this activity consists of several stages, namely the planning stage, delivery of material and discussion and continued online discussion. Based on the input obtained from the participants, this activity is very useful for the participants and motivates the participants to improve the competencies that students must have in entering the Era of Digital Society Transformation 5.0. No less important contribution of this activity for lecturers is to be able to increase understanding of appropriate learning methods for students who will enter the Transformation Era Digital Society 5.0. This activity concluded that the education provided by the resource persons could be well understood by students. The knowledge includes 1.) student challenges, 2.) student opportunities and 3.) student attitudes in optimizing Opportunities and Challenges in the Transformation Era Digital Society 5.0.